2023
DOI: 10.3390/antiox12071342
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Benefits of Probiotics in Gut Inflammation and Diarrhea—From an Antioxidant Perspective

Abstract: Inflammatory bowel disease (IBD), characterized by an abnormal immune response, includes two distinct types: Crohn’s disease (CD) and ulcerative colitis (UC). Extensive research has revealed that the pathogeny of IBD encompasses genetic factors, environmental factors, immune dysfunction, dysbiosis, and lifestyle choices. Furthermore, patients with IBD exhibit both local and systemic oxidative damage caused by the excessive presence of reactive oxygen species. This oxidative damage exacerbates immune response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 120 publications
(114 reference statements)
0
11
0
Order By: Relevance
“…According to the findings of Li et al, the utilization of probiotic strains, such as Lactobacillus delbrueckii , Lactobacillus fermentum , and Bacillus coagulans TL3, resulted in the activation of the Nrf2/Ho-1 pathway. Consequently, this activation facilitated the confrontation of oxidative stress and the inhibition of ulcerative colitis 9 . Gao et al demonstrate that the utilization of the probiotic Saccharomyces boulardii may potentially exhibit antioxidant efficacy by augmenting the levels of antioxidant enzymes (superoxide dismutase, catalase, and heme oxygenase 1) and glutathione, while concurrently reducing the accumulation of malondialdehyde 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the findings of Li et al, the utilization of probiotic strains, such as Lactobacillus delbrueckii , Lactobacillus fermentum , and Bacillus coagulans TL3, resulted in the activation of the Nrf2/Ho-1 pathway. Consequently, this activation facilitated the confrontation of oxidative stress and the inhibition of ulcerative colitis 9 . Gao et al demonstrate that the utilization of the probiotic Saccharomyces boulardii may potentially exhibit antioxidant efficacy by augmenting the levels of antioxidant enzymes (superoxide dismutase, catalase, and heme oxygenase 1) and glutathione, while concurrently reducing the accumulation of malondialdehyde 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these effects, probiotics have also been shown to possess antioxidant properties. These properties involve the removal of reactive oxygen species, the binding of metal ions to prevent the Fenton reaction, which is defined as the oxidation of organic contaminants by hydrogen peroxide and Fe (II), and the control of host antioxidant enzymes 9 . Henceforth, it can be postulated that the utilization of probiotics may serve as a prospective approach in regulating the detrimental consequences that manifest in IBD.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Crohn's disease exhibits skip lesions, transmural inflammation, the presence of granulomas, fistulae, and frequent involvement of the terminal ileum (James, 2014). The utilization of probiotics in patients with IBD has risen by 50% in recent years due to increasing evidence supporting the efficacy of specific probiotic strains for treating and preventing IBD, demonstrated in both animal models and human studies (Li et al, 2023). Lactobacilli and Bifidobacteria, two frequently employed probiotics, have been identified for their capacity to enhance antioxidant status in individuals with Inflammatory Bowel Disease (IBD).…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…However, immune health can be influenced by a combination of genetic and immunological factors, as well as lifestyle choices, infections, and hormone imbalances, making the relationship between nutrition and immune function complex [ 34 , 38 ] Nowadays, probiotics have attracted researchers across the globe for their widespread beneficial health-promoting properties, especially in irritable bowel syndrome and antibiotic-associated diarrhea [ 39 ]. Some studies in inflammatory bowel diseases have suggested that probiotics may have a positive impact on specific aspects of Inflammatory Bowel Disease (IBD) [ 39 , 40 , 41 ]. However, more research is still needed to fully understand their potential benefits [ 42 ].…”
Section: Introduction: Probiotics As Novel Solutions To Old Problemsmentioning
confidence: 99%